Performance of two-flux and four-flux models for predicting the spectral reflectance and transmittance factors of flowable dental resin composites - Duveiller, Vincent (2023)
Objective: To evaluate the prediction accuracy of the Kubelka-Munk Reflectance Theory and other more innovative two-flux and four-flux models for predicting the reflectance and transmittance factors of two flowable dental resin composites of various thicknesses within clinically acceptable color difference. Methods: Cylindrical samples of Aura Easy Flow resin composite (Ae1, Ae2, Ae3, Ae4 shades) and Estelite Universal Flow SuperLow resin composite (A1, A2, A3, A3.5, A4, A5 shades) were prepared with thicknesses ranging from 0.3 mm to 1.8 mm. Their reflectance and transmittance factors were measured with a spectrophotometer based on an integrating sphere, and were also predicted by 3 different two-flux models and 2 different four-flux models. The accuracy of reflectance and transmittance factor predictions was assessed using the CIEDE2000 color distance metric and 50:50% acceptability and perceptibility threshold criteria. Results: Eymard's four-flux model is found to be the most accurate for predicting the spectral reflectance and transmittance factors, with 85% (resp. 100%) of all color deviations below the acceptability threshold, and below the perceptibility threshold for 40% (resp. 57%) of the samples with thickness ranging from 0.3 to 1.8 mm in reflectance (resp. transmittance) mode. The Kubelka-Munk Reflectance Theory is found to be the least accurate model for predicting the spectral reflectance and transmittance factors of dental resin of thickness ranging from 0.3 to 1.8 mm. Significance: Eymard's four-flux model enables to predict the color of slices of dental materials within acceptable color differences. Eymard's four-flux model's optical parameters thus describe light-matter interactions in dental materials more accurately than state of the art Kubelka-Munk Reflectance Theory.